Sustainable Recycling Techniques of Pavement Materials - Li, Qiang; Wang, Jiaqing; Huang, Kaijian; Ge, Dongdong; Gong, Fangyuan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on experimental and applied research on sustainable recycling techniques for pavement materials. The recycling of waste materials in pavement infrastructures could be successfully facilitated based on such techniques. Sustainability in civil engineering has attracted more attention in recent decades, the lack of natural resources, serious environmental pollution, and high carbon dioxide emissions are the main issues regarding traditional infrastructure materials. This book provides the most recent innovations and applications of recycling wastes as high-performance pavement materials, aiming to provide methods for producing green low-carbon and durable pavement structures. In particular, several treatment methods and 3D construction techniques are proposed for the efficient recycling of waste materials.